Metabolic Responses to Epinephrine by Periparturient Dairy Cows Fed Prepartum Diets Differing in Predicted Metabolizable Protein Supply - Underwood, John P.; Drackley, James K. (Frontiers in Animal Science, 2022)
We determined the effects of prepartum dietary metabolizable protein (MP) supply on lipolytic and glucose response to epinephrine stimulus during the periparturient period. Twelve non-lactating cows in second or greater pregnancies were assigned to a low MP (LMP) diet formulated to provide ~900 g/day MP or a high MP (HMP) diet to provide ~1,100 g/day MP. Cows received prepartum diets from 28 days before expected parturition to day of parturition and then received a common lactation diet until 35 days postpartum. Blood was sampled weekly to day −7, daily to day 7, and weekly through day 35 relative to parturition for analysis of glucose, non-esterified fatty acids (NEFAs), 3-hydroxybutyrate (BHB), urea N, and total protein concentrations. Epinephrine challenges were conducted on day −10 before expected parturition and days 7 and 14 postpartum. Epinephrine [1.4 μg/kg body weight (BW)] was administered via jugular vein and blood was collected from the opposite jugular vein from −45 min to +120 min relative to epinephrine administration. Plasma was analyzed for glucose and NEFA concentrations. Prepartum dry matter intake (DMI) (14.7 and 12.6 ± 1.5 kg/day for LMP and HMP, respectively), postpartum DMI (21.4 and 19.4 ± 1.3 kg/day for LMP and HMP, respectively), and 4% fat-corrected milk (FCM) (37.0 and 36.8 ± 1.5 kg/day for LMP and HMP, respectively) did not differ significantly between diets. Cows fed HMP had higher plasma concentrations of urea N prepartum than cows fed LMP (14.0 vs. 7.9 ± 0.8 mg/dl). Cows fed HMP tended to have greater prepartum concentrations of total protein in plasma than those fed LMP (7.5 vs. 7.0 ± 0.2 g/dl). The area under the curve (AUC) for NEFA response to epinephrine did not differ between diets, but differed by day relative to parturition [8,284, 29,018, and 18,219 ± 2,302 min × (μeq/l) for days −10, 7, and 14, respectively]. Maximal response of NEFA concentration to epinephrine was greater for HMP than for LMP (744 vs. 438 ± 72 μeq/l). The glucose AUC did not differ between diets or among days. Lipolytic response, but not glucose response, to epinephrine was enhanced during the early postpartum period relative to the late dry period. However, those responses were not affected by prepartum MP supply.